Longitudinal Trends of Prevalence of Neutralizing Antibody against Human Cytomegalovirus over the Past 30 Years in Japanese Women - Shibamura, Miho; Yamada, Souichi; Yoshikawa, Tomoki; Inagaki, Takuya; Nguyen, Phu Hoang Anh; Fujii, Hikaru; Harada, Shizuko; Fukushi, Shuetsu; Oka, Akira; Mizuguchi, Masashi; Saijo, Masayuki (Japanese Journal of Infectious Diseases, 2022)
Neutralizing antibodies (NAbs) to human cytomegalovirus (HCMV) are associated with the risk of transplacental HCMV infection of the fetus in pregnant women. The IgG-positivity rate to HCMV determined by enzyme immunoassay (EIA) or indirect immunofluorescence assay has decreased from approximately 100% to 70% over the past 30 years in Japan. We tested serum samples from 630 Japanese women aged 20–49 years whose blood samples were obtained between 1980 and 2015. IgG titer was measured using an EIA-based assay. HCMV-NAb titer was measured using a neutralization test assay with an HCMV isolate on human retinal epithelial cells. Longitudinal transitions in HCMV-NAb prevalence were clarified. The prevalence of HCMV-EIA-IgG, and HCMV-NAb at a titer of 16-fold, and HCMV-NAb at a titer of 100-fold, changed from 96.7% to 78.9%, 93.3% to 85.6%, and 35.5% to 41.1%, respectively, between 1980–1990 and 2010–2015. Prevalence of HCMV-NAb at a titer of 16-fold decreased by 7.7%, whereas that at a titer of 100-fold increased by 5.6%. A high titer of HCMV-NAb in pregnant women is expected to reduce the risk of intrauterine HCMV transmission from the mother to the fetus. The association between the risk of congenital HCMV infection and the prevalence of HCMV-NAb remains to be addressed.